2020
DOI: 10.1101/2020.07.07.191817
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Divergent strategies to reduce stomatal pore index during water deficit in perennial angiosperms

Abstract: Summary⍰ Modulation of stomatal development may be an acclimation response to low water availability. However, stomatal development plasticity has been assessed in very few species.⍰ We quantified leaf anatomy traits, including stomatal index (SI), density (SD), size (SS), and pore index (SPI), in response to water-deficit stress in river birch (Betula nigra L.), eastern redbud (Cercis canadensis L.), and si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 109 publications
(109 reference statements)
1
0
0
Order By: Relevance
“…This explains the observed positive correlation between SP and the physiological traits in B. schmidtii based on the PCA plot. The result found in B. schmidtii is consistent with results reported in Mano et al (2020) , who reported a significant reduction in the stomata pore area of Betula nigra L. in response to water stress via stomatal development plasticity. The author further noted that despite such a significant decrease, there was only a minor to no effect on the stomatal conductance of the species.…”
Section: Discussionsupporting
confidence: 91%
“…This explains the observed positive correlation between SP and the physiological traits in B. schmidtii based on the PCA plot. The result found in B. schmidtii is consistent with results reported in Mano et al (2020) , who reported a significant reduction in the stomata pore area of Betula nigra L. in response to water stress via stomatal development plasticity. The author further noted that despite such a significant decrease, there was only a minor to no effect on the stomatal conductance of the species.…”
Section: Discussionsupporting
confidence: 91%